Complications After Soft Tissue With Plate vs Bony Mandibular Reconstruction: A Systematic Review and Meta-analysis. (March 2021) - Bauer, Eric; Mazul, Angela; Zenga, Joseph; Graboyes, Evan M.; Jackson, Ryan; Puram, Sidharth V.; Doering, Michelle; Pipkorn, Patrik
Objective: Mandibular reconstruction for segmental defects is a well-studied topic. However, there are conflicting data on the risks of delayed plate-related complications. The objective of this systematic review and meta-analysis was to assess long-term plate-related complications following reconstruction of the mandible with soft tissue and a plate as compared with immediate vascularized bony reconstruction. Data Sources: A medical librarian created search strategies with a combination of keywords and controlled vocabulary in Ovid Medline (1946–), Embase (1947–), Scopus (1960–), Cochrane Central Register of Controlled Trials, Cochrane Database of Systematic Reviews, and Clinicaltrials.gov. Review Methods: Candidate articles were independently reviewed by 2 authors. Inclusion/exclusion criteria were uniformly applied. Articles were considered eligible if they included adequate reporting of plate extrusion and/or fracture and had follow-up ≥12 months. Results: A total of 2379 patients were included. The risk of plate fracture was low in cases of soft tissue with a plate (5%; 95% CI, 0.03-0.08) and osseous reconstruction (1%). The risk of extrusion following soft tissue and plate reconstruction was 20% (95% CI, 0.15-0.27). In the osseous reconstruction group, the risk of extrusion was 10% (95% CI, 0.06-0.18). Revision surgery was performed twice as often following soft tissue with a plate as compared with vascularized bony reconstruction (32% [95% CI, 0.25-0.40] vs 14% [95% CI, 0.09-0.21], respectively). Conclusion: Delayed plate-related complications remain a significant problem following segmental defect reconstruction. Soft tissue and plate reconstruction techniques may increase the risk of plate removal and revision surgery.